PROBLEM-BASED METHODS IN THE EDUCATIONAL PROCESS - Sultonov Ravshanbek Rustamovich; Isomaddinova Umida Mamurjonovna (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract.  In  this  article,  the  model  of  problem-based  education  in  the educational process is designed for students' thinking, creating a problem situation in children's  minds  by  posing  problems  in  education;  looking  for  ways  to  solve  the problem, making assumptions; application of the chosen method to the execution of a hypothetical problem; drawing a conclusion on the completed problem, strengthening knowledge by applying the drawn conclusion to practice.